The association between cannabis use and psychiatric comorbidity in people with personality disorders: A population-based longitudinal study. (August 2019) - Shalit, Nadav; Rehm, Jürgen; Lev-Ran, Shaul
Highlights: There is more psychiatric comorbidity in people with PD who use cannabis. There are more incident substance use disorders in people with PD who use cannabis. Rates of incident opioid use disorders are higher among people with PDs who use cannabis. Cannabis use and PD generally have no interaction. Abstract: Both personality disorders (PD) and cannabis use are highly comorbid with various psychiatric disorders. While previous research indicates specific interactions between cannabis use and schizotypal PD associated with schizophrenia, research into cannabis use among individuals with other PDs and the development of several additional psychiatric disorders is scarce. We explored the prevalence and incidence of psychiatric disorders among individuals with PDs who use cannabis, and whether individuals with PDs who use cannabis are at increased risk for developing psychiatric disorders compared to cannabis users without a PD. Finally, we examined the interaction effect between cannabis use and personality disorders on comorbid psychiatric disorders. Data from 34, 653 participants in waves 1 and 2 of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) were analyzed. Our findings indicate that individuals with PDs who used cannabis were at increased odds for developing substance use disorders (including opioid use disorder), but not other comorbid psychiatric disorders, at 3-year follow up. No significant interaction effects were generally found between cannabis use and PD. These findings suggest that aside from specific substance use disorders, individuals with PDs are not at an increased risk for developing other psychiatric disorders following cannabis use.